Rana in potovanje - Sofoklejev Filoktet in Homerjeva Odiseja v drami in uprizoritvi Inflammation du verbe vivre (Vnetje glagola živeti) Wajdija Mouawada - Pogorevc, Petra (Amfiteater (Ljubljana), 2021)
In her article, the author analyses an example of a text and its staging brought about by the sudden death of a member of the playwright’s creative team. In his solo performance Inflammation du verbe vivre (Inflammation of the Verb To Live), created at the Paris Théâtre National de la Colline in 2015, Canadian-Lebanese playwright, director and actor Wajdi Mouawad interwove the ancient Greek literary and mythological heritage with a personal confession about the loss of his friend and professional colleague Robert Davreu, upgrading it with a socially critical depiction of the situation in today’s Greece. The performance was made as the penultimate part of a staging cycle of Sophocles’s seven preserved tragedies under the common title Le dernier jour de sa vie (The Last Day of his Life). Mouawad had intended to direct the cycle in new translations by Davreu. Mouawad thus connected the process of mourning the death, which stopped the project, with the documentation of the writing process of the text that he later also directed and performed in the form of a peculiar theatre elegy. He fused the character of Philoctetes with the character of Odysseus; not the Odysseus from Sophocles’s tragedy who plots to steal Philoctetes’s bow, but the one from Homer who seeks his way home to Ithaca for ten years after the conquer of Troy and visits Tiresias’s shade in the underworld.
Keywords: ancient period; antika; body; death; ep; epic; gender; gledališče; lament; mit; mourning; myth; prerokba; prophecy; rana; smrt; sol; telo; theatre; tragedija; tragedy; wound; žalostinka; žalovanje